2020
DOI: 10.1108/jiabr-07-2017-0104
|View full text |Cite
|
Sign up to set email alerts
|

Foreign directors and corporate governance in Islamic banks

Abstract: Purpose The purpose of this paper is to examine whether foreign directors’ influence on opportunistic behavior among managers varies between Islamic banks (IBs) and conventional banks (CBs). It also examines how religious ethics and morals guide foreign directors to be better monitors. Design/methodology/approach A panel fixed effects regression is used to analyze the effect of foreign directors on opportunistic behavior among managers in IBs and CBs. The authors use different proxies such as loss avoidance,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 86 publications
1
17
3
Order By: Relevance
“…This finding implies that the proportion of foreign directors does not affect the financial soundness of Islamic banks. This result contradicts the agency theory and suggestions of previous research (Daly and Frikha, 2015; Ramly et al , 2018; Mansoor et al , 2019; Almutairi and Quttainah, 2020). A possible explanation that may justify this finding is that the governance standards (AAOIFI and IFSB) do not impose requirements on the presence of foreign directors and remain silent.…”
Section: Resultscontrasting
confidence: 90%
See 1 more Smart Citation
“…This finding implies that the proportion of foreign directors does not affect the financial soundness of Islamic banks. This result contradicts the agency theory and suggestions of previous research (Daly and Frikha, 2015; Ramly et al , 2018; Mansoor et al , 2019; Almutairi and Quttainah, 2020). A possible explanation that may justify this finding is that the governance standards (AAOIFI and IFSB) do not impose requirements on the presence of foreign directors and remain silent.…”
Section: Resultscontrasting
confidence: 90%
“…In this regard, directors must ensure compliance with Shari’ah rules and verify that the Shari’ah corporate governance framework is compatible with the size and the nature of activities of the banks (IFSB, 2006; AAOIFI, 2010; BNM, 2010). Hakimi et al (2018) and Almutairi and Quttainah (2020) say that the Board of Directors’ effectiveness depends on its composition, which can affect the corporate governance of Islamic banks. That’s why this study aims to empirically diagnose the impact of the Board of Directors’ characteristics on the financial soundness of Islamic banks.…”
Section: Discussionmentioning
confidence: 99%
“…Almutairi and Quttainah (2017) conducted a study on a sample of 100 IBs from 1993 to 2014 and found that the number of outside directors on a SB is positively correlated with the IB's performance. Almutairi and Quttainah (2020) add that the SB works with the director during its meetings to improve positive managerial behavior. Ramly et al (2018) assert that together, the SB and the director prevent managers from taking excessive risks, thereby improving financial soundness.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…As a result, Islamic financial institutions (IFIs) are subject to a dual governance structure with both the SB and the board of directors (BODs), which makes their governance framework more powerful than that of conventional financial institutions (Alam et al, 2020). Almutairi and Quttainah (2020) add that the SB approves banking transactions and services, whereas the BOD is responsible for the overall corporate governance. Thus, the BOD and the SB enhance the credibility and confidence level of stakeholders.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation